When Scaffolding is Not Helpful - Bare, Catherine; Simon, Leah (Ohio Journal of School Mathematics, 2017)
During a field placement as pre-service high school teachers, we developed and implemented two versions of a rich mathematical task. When reviewing our students’ work, we observed that they had not applied the specific concepts we had intended—due, in part, to the level of scaffolding we had provided. Reflecting on this, we developed a rubric to guide our scaffolding of rich tasks based on task purpose.